Identification and characterization of outer membrane proteins of Pasteurella multocida serotype D by using monoclonal antibodies. - Marandi, M V (1995)
Monoclonal antibodies (MAbs) against Pasteurella multocida serotype D were obtained by fusion of spleen cells from BALB/c mice immunized with outer membrane proteins (OMPs) with SP2/0-Ag 14 murine myeloma cells. Desirable MAbs were selected by enzyme-linked immunosorbent assay (ELISA) with OMP as the antigen. MAbs MT1 and MT2 identified two different proteins (H [heavy] and W [weak]), each with a molecular mass of 32 kDa, in Western blots (immunoblots). Treatment of the OMPs with proteolytic enzymes and sodium periodate indicated that the binding sites of MAbs MT1 and MT2 are of protein and glycoprotein natures, respectively. The epitopes reactive with MAbs were surface exposed, as visualized by immunoelectron microscopy. Among field isolates of P. multocida serotype D, two distinct OMP patterns were recognized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and these patterns were designated types I and II. In both the ELISA and the Western blot, MAb MT1 recognized only type I isolates, whereas MAb MT2 recognized both type I and II isolates. Neither MAb MT1 nor MAb MT2 reacted with either reference strains of capsular serotypes A, B, E, and F or field isolates of capsular serotype A of P. multocida. This is the first report of MAbs identifying the serotype D-specific OMP of P. multocida.